Activity spaces in studies of the environment and physical activity: A review and synthesis of implications for causality. (July 2019) - Smith, Lindsey; Foley, Louise; Panter, Jenna
Abstract: Activity spaces are increasingly used to understand how people interact with their environment and engage in activity but their use may raise challenges regarding causal inference. We conducted a systematic review of findings and the methodological, analytical and conceptual issues relevant to causal inference. Studies were included if they comprised a spatial summary of locations visited, assessed any part of the causal pathway between the environment, physical activity and health, and used quantitative or qualitative methods. We searched seven electronic databases in January 2018 and screened 11910 articles for eligibility. Forty-seven studies were included for review. Studies answered research questions about features of or environmental features within activity spaces using a range of spatial and temporal summary techniques. The conceptual challenge of using activity spaces to strengthen causal inference was rarely considered, although some studies discussed circularity, temporality, and plausibility. Future studies should use longitudinal and experimental designs and consider the potential and actual use of spaces for physical activity, and their relationship with total levels of activity. Highlights: We reviewed studies that investigated the environment-physical activity relationship using activity spaces. Studies assessed the features of (shape or size) or within activity spaces. A range of spatial and temporal methods were employed to define activity spaces and answer different research questions. Most studies were cross-sectional and casual inference was rarely discussed. Evaluation of interventions using longitudinal or qualitative data would be useful to strengthen causal inference.